Budget reforms in Russia: results and perspectives - Komyagin, Dmitry (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The article covers budget reforms in Russia which have been taking place since 1991. It presents both a mutli-perspective and retrospective glance at the modern reforms, and their continuity with regard to other Russian reforms from the historical past is discovered.Changes in the Russian legislation regulating budgetary relations and changes to inter-budgetary relations and the budgetary process are analyzed in details. The article contains a review of program documents describing the course of reform and a prediction of future changes.